APPLICATION SHIFTING THE BURDEN OF PROOF IN SYARIAH CRIMINAL CASES UNDER THE SYARIAH COURT EVIDENCE ENACTMENT IN MALAYSIA - Saifuddin, Suhaizad; Ali Tajuddin, Hanifah Haydar (Journal of Shariah Law Research, 2024)
Burden of proof is one of the significant aspects in the Syariah Court Evidence Enactment. Inaccurate application of burden of proof and shifting the burden of proof could affect a just handling and outcome of a case. Brief analysis found that the inaccuracy issues seemed to be caused by misunderstandings and different interpretations among the Syariah law practitioners. Thus, the objective of this paper is to mainly identify the legal provisions relating to burden of proof and shifting the burden of proof in the Syariah Court Evidence Enactment. Besides, the paper also aims to analyse cases in the Syariah court that considered issues relating to the application of burden of proof and shifting the burden of proof in syariah criminal cases. The paper adopts the legal research methodology based on the doctrinal and qualitative approach. The data is gathered through library research and documentation, which are then analysed applying critical content analysis methods. The paper finds that there are misunderstandings and different interpretation among the Syariah law practitioners relating to the application of burden of proof and its shift in syariah criminal cases. The paper is essential in explaining the application of the legal provisions relating to burden of proof and its shift in the Syariah Court Evidence Enactment. The paper will also identify issues that relate to misunderstandings among the Syariah law practitioners and subsequently, suggest improvements that can be implemented to increase the understanding among the Syariah law practitioners.